Engineering properties of seawater-mixed mortar with batching plant residual waste as aggregate replacement - Astuti, Pinta; Pramana, Alfido Adhi; Rafdinal, Rahmita Sari; Purnama, Adhitya Yoga; Arifan, Rusdi Sahla; Monika, Fanny; Habirun, Asiya Nurhasanah (SINERGI, 2024)
This research showcased the use of leftover trash as a substitute for aggregate in mortar combined with saltwater. The raw waste materials underwent analysis using X-ray fluorescence (XRF) in order to determine the component materials and crystalline phases present. The choice of Portland composite cement (PCC) was made because of its durability in a hostile environment. Seawater is used to combat the water crisis and prevent corrosion, thanks to its exceptional resistance to corrosion. The attributes of mortar were assessed in terms of its fresh characteristics (slump and flow table) as well as its mechanical properties (compressive strength, split tensile strength, flexural strength, density, and shrinkage). The findings indicate that the dried mortar waste is suitable as a patch repair material for a substrate with a strength of 20 MPa, but only when utilized in a maximum quantity of 20% and with a water-to-cement ratio of 0.3. The repaired concrete with a strength of 25 MPa did not need any waste containment and had a maximum water-to-cement ratio (W/C) of 0.3, whether combined with saltwater or tap water. The possible role of the mortar containing the dried waste was to be the species for brick and other non-structural. Additionally, the use of an alternative cementitious substance is suggested to enhance the effectiveness of the patch repair material, particularly when paired with cathodic corrosion protection in damaged concrete